PENGARUH RASIO PULLEY TERHADAP BEBAN MAKSIMAL PEMAKAIAN MESIN LISTRIK PORTABEL RAMAH LINGKUNGAN - Sugiarto, Bambang (Politeknik Harapan Bersama Tegal, 2023)
Abstract – Population growth can trigger an increase in the need for electrical energy, but this is not balanced with an increase in the supply of electricity, where the installed power capacity is fixed, while the needs of the community continue to increase and various supporting activities. Such conditions encourage the search and study of the use of new energy sources, which are renewable, environmentally friendly, and environmentally friendly which aim to produce electricity without any assistance from BBM and are expected to provide convenience in obtaining electricity. , by utilizing a 12 volt, 75 Ah battery / battery, a 12 volt dc alternator equipped with an inverter with a voltage of 1500 watts to convert DC current to AC, 500 watt ac driving dynamo, pulley with a ratio of 1,333 : 1 inch. The test was carried out with a variation of the pulley ratio of 1,333 : 1 inch, the maximum load material tested was using a 50 watt, 100 watt, 200 watt, 250 watt, 300 watt, 350 watt, 380 watt light bulb. Based on the test data using the maximum load with a pulley ratio of 1,333: 1 inch for 380 watts, the voltage drop can reach 11.4 volts more than the maximum load the portable electric machine does not work optimally. This causes the alternator to not be able to issue an electric voltage of more than 12 volts for the battery charging process, so that the inventor cannot work properly which results in a low inverter output voltage unable to provide electric current to the propulsion motor.